Is educational attainment associated with acute exposure to air pollution and pollen, and is it worse for pupils with asthma and seasonal allergic rhinitis? - Amy Mizen; Jane Lyons; Ashley Akbari; Damon Berridge; David Carruthers; Gwyneth Davies; Lorraine Dearden; Ruth Doherty; Anna Mavrogianni; Iain Lake (International Journal of Population Data Science, 2018)
Introduction There is a lack of evidence of the adverse effects of air pollution and pollen on cognition for people with air quality related health conditions. This study explored the effects of air quality and respiratory health conditions on educational attainment for 18,241 pupils across the city of Cardiff, United Kingdom.